Reimagining Trade Corridors: Regulatory Dynamics and Sustainability in Global Commerce - Muharam, Husni; Wufron, Wufron (Yayasan Sinergi Kawula Muda, 2023)
This narrative review explores the regulation of international trade, focusing on transport corridor development and its impact on sustainable global commerce. It synthesizes literature from Scopus, Web of Science, and Google Scholar, using keywords like